Cardiovascular Disease Hospitalizations in Relation to Exposure to the September 11, 2001 World Trade Center Disaster and Posttraumatic Stress Disorder. Issue 5 (24th October 2013) - Jordan, Hannah T.; Stellman, Steven D.; Morabia, Alfredo; Miller‐Archie, Sara A.; Alper, Howard; Laskaris, Zoey; Brackbill, Robert M.; Cone, James E.
Abstract : Background: A cohort study found that 9/11‐related environmental exposures and posttraumatic stress disorder increased self‐reported cardiovascular disease risk. We attempted to replicate these findings using objectively defined cardiovascular disease hospitalizations in the same cohort. Methods and Results: Data for adult World Trade Center Health Registry enrollees residing in New York State on enrollment and no cardiovascular disease history (n=46 346) were linked to a New York State hospital discharge–reporting system. Follow‐up began at Registry enrollment (2003–2004) and ended at the first cerebrovascular or heart disease (HD) hospitalization, death, or December 31, 2010, whichever was earliest. We used proportional hazards models to estimate adjusted hazard ratios (AHRs) for HD (n=1151) and cerebrovascular disease (n=284) hospitalization during 302 742 person‐years of observation (mean follow‐up, 6.5 years per person), accounting for other factors including age, race/ethnicity, smoking, and diabetes. An elevated risk of HD hospitalization was observed among women (AHR 1.32, 95% CI 1.01 to 1.71) but not men (AHR 1.16, 95% CI 0.97 to 1.40) with posttraumatic stress disorder at enrollment. A high overall level of World Trade Center rescue and recovery–related exposure was associated with an elevated HD hospitalization risk in men (AHR 1.82, 95% CI 1.06 to 3.13; P for trend=0.05), but findings in women were inconclusive (AHR 3.29, 95% CI 0.85 to 12.69; P for trend=0.09). Similar associations were observed specifically with coronary artery disease hospitalization. Posttraumatic stress disorder increased the cerebrovascular disease hospitalization risk in men but not in women. Conclusions: 9/11‐related exposures and posttraumatic stress disorder appeared to increase the risk of subsequent hospitalization for HD and cerebrovascular disease. This is consistent with findings based on self‐reported outcomes.